2021
DOI: 10.4018/ijisscm.287864
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Optimization of Green Supply Chain Management Mode of Agricultural Enterprises in the Digital Economy

Abstract: Digital economy is a rapidly developing economic form under the background of the information age. This article introduces the construction and optimization of the green supply chain management model of agricultural enterprises under the digital economy, and intends to provide some ideas and directions for the development of green supply chain management of agricultural enterprises based on digital economy. This paper proposes the construction and optimization research methods of the green supply chain managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Enterprise management in the context of digital economy, first of all, can effectively strengthen the information sharing and connection of internal management. Through digital technology, the information resources of various departments and levels within the enterprise have changed from the traditional regular or irregular sharing of emails and meetings to the direction of real-time open sharing of information resources between departments and levels, allowing information exchange and communication between departments and levels [3]. It is more smooth, reduces information barriers, and provides convenience for enterprise management.…”
Section: Improve the Openness Of Enterprise Managementmentioning
confidence: 99%
“…Enterprise management in the context of digital economy, first of all, can effectively strengthen the information sharing and connection of internal management. Through digital technology, the information resources of various departments and levels within the enterprise have changed from the traditional regular or irregular sharing of emails and meetings to the direction of real-time open sharing of information resources between departments and levels, allowing information exchange and communication between departments and levels [3]. It is more smooth, reduces information barriers, and provides convenience for enterprise management.…”
Section: Improve the Openness Of Enterprise Managementmentioning
confidence: 99%
“…Research on digital food supply chains has been reported in the literature, showing trends towards digital transformation in the agri-food industry (Hu & Li, 2022). Nakandala et al (2017) conduct an extensive literature review on information integration in fresh food supply chains, suggesting that companies adopt technology to improve the flow of information in fresh food supply chains.…”
Section: Digital Platforms In Food Supply Chainsmentioning
confidence: 99%
“…Its relevant research has mainly focused on agricultural product supply chain synergy and agricultural service supply chain synergy. In terms of agricultural products supply chain synergy, relevant documents are mainly from the perspective of cold chain logistics, information technology, logistics and supply chain finance (Peng et al, 2017;Li et al, 2019;Ji and Yuqing, 2019), studies the problem of realizing the organic combination of basic functions such as transportation, storage, processing, loading and unloading, packaging, circulation and information processing (Ghane-Ezabadi and Vergara, 2016), also proposed the inventory synergy strategy, planned synergy strategy, multimodal transport synergy strategy (Fried et al, 2017;Dai and Luo, 2017); in the agricultural service supply chain synergy, on the basis of summarizing and drawing on the "US-Canada Model," "Dutch Model," "East Asian Model," "Island Model" and other development models (Hu and Zheng, 2013), analyzes the mode of logistics cooperative management such as agricultural supply chain logistics, logistics alliance and e-commerce enterprises, and the mode of logistics enterprises such as agricultural third-party logistics and fourth-party logistics mode (Ghadiyali et al, 2018;Stefansson, 2006), explores the synergy of agricultural logistics resources such as functional synergy and structure synergy, and put forward the knowledge synergy strategy, contract synergy strategy, information synergy strategy, etc. (Ghane-Ezabadi and Vergara, 2016;Zaiqing, 2017).…”
Section: Related Research On Agricultural Logistics Synergymentioning
confidence: 99%